2009
DOI: 10.1021/la803220z
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Containing Membranes for the Catalytic Reduction of Nitroaromatic Compounds

Abstract: Layer-by-layer deposition of polyelectrolyte/metal nanoparticle films in porous alumina, track-etched polycarbonate, and nylon substrates yields catalytic membranes. With all three substrates, scanning electron microcopy images demonstrate a high density of well-separated nanoparticles in the membrane pores. These nanoparticles catalyze the reduction of nitroaromatic compounds by sodium borohydride with rate constants that are the same as those for nanoparticles immobilized on alumina powder. Moreover, the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 49 publications
2
96
1
Order By: Relevance
“…One possible reason for this is that reaction processes of nitrotoluene and nitrochlorobenzene are more complicated than those of nitroaniline and nitrophenol (Zeng et al, 2013). For example, the reduction of nitrotoluene and nitrochlorobenzene can produce amino and nitroso form products while nitroaniline and nitrophenol can only be converted into corresponding anilines in the presence of NaBH 4 and catalyst (Dotzauer et al, 2009). These results indicate the generality and the efficacy of our new catalyst toward the reduction of different nitrobenzene and we will do more works on the catalytic reaction mechanism of these nitrobenzenes in the future research.…”
Section: Catalytic Capabilitymentioning
confidence: 99%
“…One possible reason for this is that reaction processes of nitrotoluene and nitrochlorobenzene are more complicated than those of nitroaniline and nitrophenol (Zeng et al, 2013). For example, the reduction of nitrotoluene and nitrochlorobenzene can produce amino and nitroso form products while nitroaniline and nitrophenol can only be converted into corresponding anilines in the presence of NaBH 4 and catalyst (Dotzauer et al, 2009). These results indicate the generality and the efficacy of our new catalyst toward the reduction of different nitrobenzene and we will do more works on the catalytic reaction mechanism of these nitrobenzenes in the future research.…”
Section: Catalytic Capabilitymentioning
confidence: 99%
“…4-aminophenol (4-AP) was formed upon catalytic hydride reduction of 4-nitrophenol (4-NP) with sufficient amount of NaBH 4 4 allowed a rapid comparison of catalytic activities of all three types. For each type of Au nanocatalyst, the spectral studies revealed that the 400 nm peak progressively decreased to 300 nm with time due to absorption of 4-AP (Dotzauer et al 2009;Kuroda et al 2009). The conversion of 4-NP to 4-AP was studied spectrophotometrically in time-dependent absorption.…”
Section: Application Of Aunps As Catalyst In 4-nitrophenol Reductionmentioning
confidence: 99%
“…Using similar approach the same group has reported the effectiveness of the catalytic membrane system for the reduction of PNP on three different substrates namely, porous alumina, track-etched polycarbonate, and nylon [30]. These membranes selectively catalyze the reduction of nitro groups in compounds containing other reducible functionalities such as cyano, chloro, and styrenyl moieties.…”
Section: Dye Degradationmentioning
confidence: 99%